Work motivation factors among selected public and private sector employees - Elnour, Anwar S. (Pangasinan : [s.n.], 2017)
This descriptive study with use of survey method was employed to determine the work motivation factors among selected public and private sector employees in Khartoum City, Sudan (2017). The purpose of the study was to determine the work motivation factors among selected public and private sector employees in Khartoum City, Sudan using the questionnaire developed by Dr. Kovach to determine the motivation preferences based on ten questions that the participants of the study place in rank order.
Bibliography: pages 94-98.
CHED-La Union
Keywords: Employee motivation